Role of Strategic Management Factors in Educational Operations towards Improving Quality and Delivery of Education - Valliappan Raju, Assoc. Prof. Dr.; Md Rom Bin Tamjis, Prof Dr. (International Journal of Engineering and Technology, 2019)
In the recent decades, one of the areas that have gained growing scholarly interest involves the importance of and need for instructive changes. Major focus has been on major factors through which the administrative groups might achieve the desired change. In this paper, the main aim is to examine crucial factors that shape the success of administrative groups in steering instructive changes. The paper strives to propose major strategies through which the selected goal of improving instructive approaches might be realized, especially from the context of schools. To implement any perceived or proposed changes, it becomes imperative to highlight that schools or educational institutions, led by their administrative teams, are expected to play a leading role. Overall, improved academic performance is projected to be a central outcome accruing form improvements that come in terms of instructive changes. However, the success of the change depends on the level of cooperation among the concerned human resources or expertise. Imperative to note further is that the ability of administrative groups or teams to establish a positive and supportive school environment in which the instructive changes take place also determines the degree of success in change implementation. The emerging theme is that instructive changes promise to steer improvements but success depends on how different parties play specific roles expected of them.Â
Keywords: Strategic Management; Educational Institutions